2020
DOI: 10.3390/plants9101258
|View full text |Cite
|
Sign up to set email alerts
|

Inflorescence Development and Floral Organogenesis in Taraxacum kok-saghyz

Abstract: Rubber dandelion (Taraxacum kok-saghyz Rodin; TK) has received attention for its natural rubber content as a strategic biomaterial, and a promising, sustainable, and renewable alternative to synthetic rubber from fossil carbon sources. Extensive research on the domestication and rubber content of TK has demonstrated TK’s potential in industrial applications as a relevant natural rubber and latex-producing alternative crop. However, many aspects of its biology have been neglected in published studies. For examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
(103 reference statements)
1
7
0
Order By: Relevance
“…Each floret was composed of five united petals represented by the corolla, as well as five fused stamens building the anther tube [ 41 ]. Following the onset of flowering, the stigma grows through the anther tube to expose the receptive site of the forked stigma for potential pollinators, carrying the pollen at the outer cuticula.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each floret was composed of five united petals represented by the corolla, as well as five fused stamens building the anther tube [ 41 ]. Following the onset of flowering, the stigma grows through the anther tube to expose the receptive site of the forked stigma for potential pollinators, carrying the pollen at the outer cuticula.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, detailed microscopic studies of pollen–stigma interactions and pollination in T. koksaghyz have not been reported thus far. Previous studies have shown morphological differences between T. officinale and T. koksaghyz in terms of flower and seed structure [ 40 ], and have cataloged the morphological appearance of the T. koksaghyz capitulum and floral organogenesis in more detail [ 41 ]. Accordingly, we studied the pollen–stigma interaction mechanism in T. koksaghyz after incompatible and compatible pollination and investigated the gene expression profiles during pollination and pollen tube growth.…”
Section: Introductionmentioning
confidence: 99%
“…To decide on pappus–sepal homology, we first observed the floral development of dandelion micromorphologically ( Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 and Figure 6 ; Supplementary Figures S1–S5 and Video’s SV1 and SV2 ) and defined the different stages of floral initiation, floral maturation, and seed formation ( Table 1 ). Well-defined stages of floral ontogenesis are available for some model species, particularly Arabidopsis [ 63 ], but in the Asteraceae the main focus has been on the inflorescence and not florets development, for instance in Gerbera [ 64 ], with additional floral initiation stages in [ 65 ], and recent studies in Chrysanthemum [ 66 ], lettuce [ 53 ], and the rubber dandelion ( T. kok-saghyz ) [ 67 ]. Our study concerns the floret development only, starting with the floral primordium as stage 1 , and is aimed as a reference for dandelions and, where possible, other Asteraceae.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of species studied by Harris [ 68 ], however, showed a pappus ring preceding the origin of many pappus part primordia on this ring, as we found in T. officinale . In T. kok-saghyz , pappus part primordia of similar sizes were seen at both the alternipetalous and antipetalous position (Figure 3F in [ 67 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, this plant is considered a rare endemic species of the flora of Kazakhstan, which has high strategic importance and stores valuable rubber and inulin. T. kok-saghyz is a mesophytic plant, loves moisture, is resistant to cold and heat, and occupies a wide ecological spectrum [7,8]. It is necessary to develop the methods of obtaining rubber, to study and use it, to prevent the destruction of the raw materials, and to pay attention to the quality.…”
Section: Introductionmentioning
confidence: 99%